Epidemiology of non-vaccine serotypes of Streptococcus pneumoniae before and after universal administration of pneumococcal conjugate vaccines - Qian-qian Du; Wei Shi; Dan Yu; Kai-hu Yao (Taylor & Francis Group, 2021)
The universal administration of pneumococcal conjugate vaccines (PCVs) had been demonstrated as an effective way to prevent Streptococcus pneumoniae infection. However, the immunity induced by PCVs protected against the infections caused by vaccine serotypes, which were usually more frequent than non-vaccine serotypes (NVTs). The prevalence and pathogenicity of NVTs after universal vaccination have caused widespread concern. We reviewed the epidemiology of non-PCV13 S. pneumoniae before and after PCV13 introduction, and explored the potential reasons for the spread of NVTs. Emerging and spreading NVTs can be regarded as the focus for future serotype epidemiological survey and vaccine optimization. Abbreviations IPD: invasive pneumococcal disease PCV: pneumococcal conjugate vaccines VT: vaccine serotypeNVT: non-vaccine serotype